Role of Vegetation in Improving Air Quality: A Literature Survey - Yasir, Ammar; Masood, Lavaiza; Syarif, Maryam; Ahmed, Zunair; Sherazi, Syeda Rameen; Sabir, Talha (Riviera Publishing, 2025)
Air pollution has become one of the most pressing environmental challenges affecting public health, urban ecosystems, and climate stability. Vegetation plays a crucial role in mitigating air pollution through various biophysical and biochemical processes, yet its effectiveness depends on multiple contextual factors. This literature survey aims to analyze and synthesize existing research on the role of vegetation in improving air quality, focusing on the mechanisms involved and the determinants that influence its performance across different environments. The study employs a systematic literature review approach, drawing from peer-reviewed journal articles, conference proceedings, and government reports published in the last two decades. The analysis highlights key mechanisms such as pollutant absorption through leaf surfaces, particulate matter deposition, and microclimate regulation that contribute to air purification. The findings also reveal that vegetation effectiveness is shaped by species characteristics, plant density, urban morphology, climatic conditions, and maintenance practices. The study concludes that strategic vegetation planning can significantly reduce urban air pollutants and enhance environmental health. These insights hold important implications for urban planners, environmental policymakers, and public health authorities in designing green infrastructure and sustainable urban landscapes. Further empirical research is recommended to quantify vegetation’s differential impact under varying ecological and socio-economic settings.